Left Atrial Volume Index as Indicator of Left Ventricular Diastolic Dysfunction: Comparation between Left Atrial Volume Index and Tissue Myocardial Performance Index - Cacciapuoti, Fulvio (Korean Society of Echocardiography, 2012)
BACKGROUND: To point out a possible correlation between left atrial volume index (LAVI) and left ventricular (LV) diastolic time interval to better define LV diastolic dysfunction, this study was performed. METHODS: In 62 hypertensive-hypertrophic patients without LV systolic dysfunction, LV volumes, myocardial mass index, ejection fraction% (EF%) and LAVI were measured by two-dimensional echocardiography. Instead, tissue Doppler echocardiography (TDE) was used to measure myocardial performance index (MPI) and its systo-diastolic time intervals, such as: iso-volumetric contraction time (IVCT); iso-volumetric relaxation time (IVRT); ejection time. LAVI, TDE-MPI and time intervals where also measured in 15 healthy controls, to obtain the reference values. RESULTS: Results shown a significant increase of LV volumes in hypertensives in comparison to the control group (p < 0.05). LV mass index also augmented (p < 0.001). Instead, EF% not significantly changed in hypertrophic patients in comparison with healthy controls. LAVI raised in hypertensives wih left ventricular hypertrophy, whereas IVCT resulted within the normal limits. On the contrary, IVRT significantly raised. Accordingly, MPI resulted higher in controls. CONCLUSION: LAVI, MPI and its time intervals appear as reliable tools to non-invasively individualize LV diastolic dysfunction in systemic hypertension, in absence of mitral valve disease.